What exactly are NESTs in Thailand?: Understanding among Thai Students Regarding the Concept of Native English Speaking Teachers in EFL Classrooms - Jenjira Jitpaiboon; Atichat Rungswang; Atinuch Pin-ngern (My University, 2025)
In Thailand, where students encounter both Native English-Speaking Teachers (NESTs) and Non-Native English Speaking Teachers (NNESTs)—with a significant portion of NNESTs being Thai and Filipino—a gap exists in understanding how Thai students interpret the terms Native English Speakers (NESs) and NESTs. This study aimed to explore this understanding among 279 Thai undergraduate students majoring in English, ranging from 1st to 4th year, focusing on their perceptions of countries considered as NES nations and using Kachru’s (1985) Three Concentric Model as a framework. It examined the relationship between students’ educational backgrounds and comprehension of these terms, as well as their expectations and experiences with NESTs and NNESTs. Data were collected via a mixed-methods approach, encompassing questionnaires and semi-structured group interviews, and analyzed using SPSS for statistical measures and AntConc for frequency analysis of questionnaire responses. Interview recordings were transcribed and analyzed for emerging themes. Key findings included that students identified countries from Kachru’s outer and expanding circles as NES nations, in addition to commonly recognized ones such as the US and the UK. The study highlighted a correlation between the students’ four-year education and their broader understanding of English. Moreover, this research found that students judge NESTs by their teaching skills and education quality rather than origin. This study underscores the importance of examining participants’ preconceptions of NESs and NESTs to enhance the accuracy of future research. It also suggests potential for further research, such as comparative studies with participants in NES countries.
Keywords: Second Language Learning and Teaching